Between Rights and Realities: Insecurity, Stigma and Marginalization Among Irani Women in the Light of Ambedkar’s Vision - Ghazaala Parveen; Shaukath Azim, (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2026)
Women’s empowerment in India is often articulated through constitutional guarantees of equality and justice; however, its lived realization remains uneven across marginalized communities. This paper examines the experiences of Irani Muslim women, a micro-minority group largely absent from mainstream academic discourse. Drawing upon Dr. B. R. Ambedkar’s framework of dignity, equality, and constitutional morality, the study explores how insecurity, stigma, and social exclusion shape their everyday lives. Using a qualitative and interpretive approach based on secondary sources and some observational insights, the paper engages with theories of social exclusion (Thorat and Kumar 2008), stigma (Goffman 1963), and capability deprivation (Sen 1999). It also situates the Irani community within broader histories of migration, cultural hybridity, and marginality (Haneda 1997; Hodgson 1974). The paper argues that Irani women occupy a position of “internal outsiders” (Mamdani 2020), where legal inclusion coexists with social exclusion. It concludes that empowerment cannot be reduced to formal rights and calls for an Ambedkarite rethinking of inclusion grounded in lived dignity.
Keywords: Irani Women; Social Exclusion; Ambedkar; Insecurity; Stigma; Marginalization; Micro-Minority